Evaluation and Comparison of Two Commercially Available Mouthrinses in Reducing Aerolised Bacteria During Ultrasonic Scaling When Used as a Preprocedural Rinse. - Asmita Ammu; Siddhartha Varma; Apurva Pisal; Girish Suragimath; Sameer Zope; Rashmi Gangavati (Cumhuriyet University, 2019)
Objective:To compare and evaluate the effect of 0.2% chlorhexidine gluconate and commercially available herbal mouthrinse in reducing aerolized bacteria when used as a preprocedural mouth rinse.Materials and Methods:A total of 45 patients were selected and randomly divided into three groups. Group I consisted of 15 patients who rinsed with distilled water for 60 seconds. Group II consisted of 15 patients who rinsed with 0.2% chlorhexidine mouthwash (Clohex®) for 60 seconds and Group III consisted of 15 patients who rinsed with herbal mouthwash (Hiora®) for 60 seconds. Aerosols produced during the oral prophylaxis procedure were collected on blood agar plates by exposing the plates at patient's and dentist's chest area and the exposed plates were incubated at 37°c aerobically for 48 hours. The number of colony forming units (CFU) in aerosol and CFU in the saliva were counted and statistically analyzed. Results:Reduction in the bacterial load using 0.2% of chlorhexidine gluconate mouthwash is found to be significant at both patient's and dentist's chest area in aerosol produced during scaling followed by herbal mouthrinse.Conclusion:The results of the present study clearly indicate that pre-procedural rinsing with 0.2% chlorhexidine gluconate was significantly more effective than herbal mouthrinse in reducing the aerolized bacteria during ultrasonic scaling. Therefore a pre-procedural rinse can significantly reduce the risk for cross contamination.